Предмет: Алгебра,
автор: goyashkatsa
Найти значение выражения
(x-4)(x-2)-(x-1)(x-3) при x=одна целая три четвертых
Ответы
Автор ответа:
0
Упростим данное выражение
(х-4)(х-2)-(х-1)(х-3)=х²-4х-2х+8-(х²-х-3х+3)=х²-4х-2х+8-х²+х+3х-3=-2х+5
При х=
получим:
(х-4)(х-2)-(х-1)(х-3)=х²-4х-2х+8-(х²-х-3х+3)=х²-4х-2х+8-х²+х+3х-3=-2х+5
При х=
получим:
Похожие вопросы
Предмет: Математика,
автор: taniyapylipiv
Предмет: Алгебра,
автор: fighterhero1232
Предмет: Математика,
автор: mvvalentina
Предмет: Математика,
автор: вика2003вика